PENGARUH KEPEMILIKAN KELUARGA DAN UKURAN PERUSAHAAN TERHADAP TAX AVOIDANCE DENGAN MANAJEMEN LABA SEBAGAI VARIABEL INTERVENING (Studi Empiris Pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2020-2021 ) - Fitri Giat Lestari (Bajang Institute, 2024)
This research investigates how family ownership and firm size influence tax avoidance, with earnings management serving as an intervening variable. The study population consists of manufacturing companies listed on the Indonesia Stock Exchange during 2020-2021. A purposive sampling method was used, yielding a sample size of 86 companies. Secondary data for this study were sourced from the Indonesia Stock Exchange within the specified period. Structural Equation Modeling was employed to test the research hypotheses. The findings reveal that family ownership and firm size do not impact earnings management. However, earnings management positively affects tax avoidance, while firm size negatively influences tax avoidance. Family ownership does not affect tax avoidance. Earnings management, as measured by discretionary accruals, mediates the effect of family ownership and firm size on tax avoidance